Prohibition of Endogamy with a Former Wife in Tigo Nagari, Pasaman: A Maslahah Mursalah Perspective - Herdianto (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study examines the customary prohibition in Tigo Nagari District, Pasaman Regency, West Sumatra, where a widower is forbidden to marry a woman from the same clan (suku) as his former wife. Unlike previous studies that focused on positive law or maqāṣid al-sharī‘ah, this research specifically analyzes the prohibition through the lens of maslahah mursalah (unrestricted public interest) within Minangkabau adat. Using a qualitative descriptive method with field research techniques—including in-depth interviews with traditional leaders (niniak mamak, datuak) and community members, as well as observation and documentation—the study finds that the prohibition stems from the community’s belief that a woman married to her former husband still maintains kinship ties with the ex-wife’s clan. Violators face social sanctions (ostracism, exclusion from village events) and material sanctions (forfeiture of inherited ancestral property, harato pusako). Such marriages are classified as sumbang (taboo) and are believed to disrupt social harmony, damage family dignity, and cause prolonged conflict. The study concludes that the prohibition carries clear benefits (maslahah) and prevents harm (mafsadah). Because it is not explicitly addressed in the Qur’an or Hadith but aligns with the objectives of Sharī‘ah—preserving social order and kinship relations—it falls under maslahah mursalah. This customary rule thus represents a legitimate application of local wisdom that does not contradict Islamic texts and serves to create harmony within the family and the broader traditional community.